Applying token economy to improve attention of child with ADHD - Irianjani, Nora Devi; Rohmah, Faridah Ainur (JECCE (Journal of Early Childhood Care and Education), 2020)
A child should be able to pay attention well during task working. But, children with Attention Deficit Hyperactivity Disorder (ADHD) experience difficulty in focusing attention or in concentrating when doing a task, both at home or at school. In the other hand, there is a behaviour modification technique that effectively proven in increasing concentration of child with ADHD.Â Â  The purpose of this study was to find out the effectiveness of token economy in improving the attention of children with ADHD when completing a task. The present study employed a single subject, a five years-old male Early Childhood Education student. The intervention was given in the form of token economy for two weeks through cooperation with parents. Observation and interviews were held to collect data regarding attention difficulty in engaging in the learning process and doing a task. The result of the study showed that there is an improvement in attention duration; the subject was able to give attention to the task in a longer duration (more than 5 minutes). The parents are expected to be more assertive and committed to applying token economy at home.